2020
DOI: 10.48550/arxiv.2001.08373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classically Simulating Quantum Circuits with Local Depolarizing Noise

Yasuhiro Takahashi,
Yuki Takeuchi,
Seiichiro Tani

Abstract: We study the effect of noise on the classical simulatability of quantum circuits defined by computationally tractable (CT) states and efficiently computable sparse (ECS) operations. Examples of such circuits, which we call CT-ECS circuits, are IQP, Clifford Magic, and conjugated Clifford circuits. This means that there exist various CT-ECS circuits such that their output probability distributions are anti-concentrated and not classically simulatable in the noise-free setting (under plausible assumptions). Firs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Here, U is a noisy-free unitary gate and X g /2 represents a bit-flip error with probability 1 2 g . We adopt the error model in [18] to describe the single bit-flip error. Of note, [18] does not provide a proof on the validity of this model, we complete the proof and extend it to multiple-error case in Section 2.3.2.…”
Section: Bit-flip Errormentioning
confidence: 99%
See 3 more Smart Citations
“…Here, U is a noisy-free unitary gate and X g /2 represents a bit-flip error with probability 1 2 g . We adopt the error model in [18] to describe the single bit-flip error. Of note, [18] does not provide a proof on the validity of this model, we complete the proof and extend it to multiple-error case in Section 2.3.2.…”
Section: Bit-flip Errormentioning
confidence: 99%
“…We adopt the error model in [18] to describe the single bit-flip error. Of note, [18] does not provide a proof on the validity of this model, we complete the proof and extend it to multiple-error case in Section 2.3.2. Using this method, we first consider the case when there is only one gate and one bit-flip error (on all qubits) in the circuit, as shown in Figure 1.…”
Section: Bit-flip Errormentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the role of noise in simplifying the simulation is ever more important, as systems grow, noise becomes more difficult to control, and it is a subtle question as to when it dominates; and even simple noise can very easily lead to breakdown of quantum speedup. Indeed, in [24][25][26][27][28][29][30] it was shown that noise generally renders the output probabilities of these devices (which in the noiseless case demonstrate quantum speedup) classically simulable efficiently. There is clearly a great need to understand better the effect of noise, and develop methods of mitigation.…”
mentioning
confidence: 99%